RNA Therapeutic Options to Manage Aberrant Signaling Pathways in Hepatocellular Carcinoma: Dream or Reality? - Sartorius, Kurt; Antwi, Samuel O.; Chuturgoon, Anil; Roberts, Lewis R.; Kramvis, Anna (Frontiers in Oncology, 2022)
Despite the early promise of RNA therapeutics as a magic bullet to modulate aberrant signaling in cancer, this field remains a work-in-progress. Nevertheless, RNA therapeutics is now a reality for the treatment of viral diseases (COVID-19) and offers great promise for cancer. This review paper specifically investigates RNAi as a therapeutic option for HCC and discusses a range of RNAi technology including anti-sense oligonucleotides (ASOs), Aptamers, small interfering RNA (siRNA), ribozymes, riboswitches and CRISPR/Cas9 technology. The use of these RNAi based interventions is specifically outlined in three primary strategies, namely, repressing angiogenesis, the suppression of cell proliferation and the promotion of apoptosis. We also discuss some of the inherent chemical and delivery problems, as well as targeting issues and immunogenic reaction to RNAi interventions.